Strategi Humas Dalam Upaya Menjaga Citra Pelindung Dan Pengayom Masyarakat - Lovia Evanne (Program Studi Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2023)
The role of public relations in the police institution is not only to build communication to carry out tasks, but also to be a means of building the image of the police. The North Lampung Police carry out the role of Public Relations through social media support in the midst of the complexity of the tasks of community service, maintenance of security and public order. This condition is formulated in a research question: What is the public relations strategy of the North Lampung Police in maintaining the image of the police as protectors and protectors of the community? The purpose of this study was to determine the North Lampung Police Public Relations Strategy in maintaining the image of the police as protectors and protectors of the community. To shed light on this issue, this research inspired the theories and concepts of public relations, social media, and institutional image. This study used a qualitative approach with data collection methods in the form of interviews and observations. The results of the North Lampung Police research carried out the Public Relations process through the stages of defining problems, designing data-based programs, holding leadership meetings to produce solutions, and carrying out program evaluations. To maintain the image of the institution, North Lampung Polres conducts outreach, listens to public complaints, uploads police achievements, responds to community suggestions, and opens communication with the public through social media Instagram, Twitter, Facebook and Youtube.